Development of the Electromagnetic Regenerative Shock Absorber as an Energy Harvesting Tool for Vehicles - Wanda Afnison; Erzeddin Alwi; Hasan Maksum; Bahrul Amin; M Yasep Setiawan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2019)
This research is a development of previous research entitled "Designing Regenerative Shock Absorber as a Vibration Energy Harvesting Tool on Vehicles" in the PUPT scheme funded by PNBP UNP 2017. In this study optimization of design oriented to energy generation was carried out while also paying attention to aspects driving comfort that might change due to the installation of a harvesting energy mechanism. One aspect of the change occurred in the type of magnet used, namely a ring type magnet with a type of neodymium material.From the test results obtained by changing the value of the efficiency of the shock absorber after the ERSA mechanism is installed by 2%, this condition also has an impact on the dissimilarity of the attenuation value obtained by 2% for the front-rear (left) and (right) wheels. In terms of generation voltage obtained the maximum generation voltage obtained is 25,600 mV. Based on the data obtained, it needs further development ERSA, especially in the aspect of the electromagnetic mechanism to optimize the generation of electrical energy.